A Study of the Impact of Supply Chain Management Practices & Customer Orientation on Hotel Operation Performance - Kachwala, Tohid (ASEAN Journal on Hospitality and Tourism, 2024)
The current study intends to examine the effects of supply chain management procedures and customer focuses on the operational effectiveness of hotels. The study surveys four hundred & five hotel managers and employees from opulent five-star hotels in Mumbai Metropolitan city. We have used Structural equation modeling to examine the given data. According to the study, efficient supply chain management procedures and a focus on customer needs have a good impact on hotel operation efficiency. Critical customer orientation practices include customer service, the best products/services in the industry, good market and customer information, and essential operations of hotel performance such as quality, speed, dependability, and flexibility. The study has identified critical supply chain management practices as strategic supplier partnership, information sharing level, and customer relationship. The results of this study shed light on the significance of supply chain management techniques and customer focus for the efficient functioning of hotels. Hotel managers should create efficient supply chain management procedures and embrace a customer-centric mindset to improve operational performance. The study did not consider the possible effects of additional contextual factors, such as hotel size, location, and market rivalry, which may impact the relationship between supply chain management methods, customer orientation, and hotel operational performance.